Deformed Classical-Quantum Mechanics Transition - Gamboa-Rios, J (American Physical Society, 2020)
An approach to study a generalization of the classical-quantum transition for general systems is proposed. In order to develop the idea, a deformation of the ladder operators algebra is proposed that contains a realization of the quantum group SU(2)q as a particular case. In this deformation Planck s constant becomes an operator whose eigenvalues approach for small values of n (the eigenvalue of the number operator) and zero for large values of n (the system is classicalized). © 2020 authors. Published by the American Physical Society. Published by the American Physical Society under the terms of the "https://creativecommons.org/licenses/by/4.0/"Creative Commons Attribution 4.0 International license. Further distribution of this work must maintain attribution to the author(s) and the published article s title, journal citation, and DOI. Funded by SCOAP3.